Endophytic bacteria as a source of novel antibiotics: An overview - Christina, Ambrose; Christapher, Varghese; J. Bhore, Subhash (Pharmacognosy Reviews, 2013)
World human population is increasing with an alarming rate; and a variety of new types of health issues are popping up. For instance, increase in number of drug‑resistant bacteria is a cause of concern. Research on antibiotics and other microbial natural products is pivotal in the global fight against the growing problem of antibiotic resistance. It is necessary to find new antibiotics to tackle this problem. The use of therapeutic plant species in traditional medicine is as old as mankind; and currently, it is strongly believed that all types of plant species across the plant kingdom do harbour endophytic bacteria (EB). The natural therapeutic compounds produced by EB do have several potential applications in pharmaceutical industry. The EB derived natural products such as Ecomycins, Pseudomycins, Munumbicins and Xiamycins are antibacterial, antimycotic and antiplasmodial. Some of these natural products have been reported to possess even antiviral (including Human Immunodeficiency Virus (HIV)) properties. Therefore, to deal with increasing number of drug‑resistant pathogens EB could serve as a potential source of novel antibiotics.
Keywords: Bioprospecting; ecomycins; human immunodeficiency virus; kakadumycins; medicinal plants; munumbicins; natural products; pseudomycins; traditional medicine; xiamycins